Internet marketing : - Roberts, Mary Lou (South-Western, 2013)
Internet Marketing: Integrating Online and Offline Strategies asserts that while the Internet is a transformational innovation, pure Internet firms do not represent the future of the Internet, as failures in recent history attest. This text builds upon the fact that the future of the Internet lies in the activities of organizations large and small--in all market spaces--that use the Internet to improve service to customers and increase organizational productivity. Many powerful e-marketers predate the Internet, have strong brand identities, and use the Internet wisely to broaden the set of options, across the marketing and logistics mix that they can offer to their customers, suppliers, and partners. The underlying paradigm in the text visualizes the Internet as a significant new channel for communications and transactions that needs to be integrated into enterprise marketing strategies. In this process, businesses are transformed from isolated entities into extended enterprises-organizations whose boundaries have become permeable, admitting both suppliers and customers into many parts of the corporate information repository and requiring their participation in many aspects of daily operations.